Sulphur Dioxide: Comparative Study of Three Analytical Methods and Determination in Malaysian Foods - Nik Mohd. Salleh, Nik Shabnam (1998)
The study was conducted in four phases. In the first phase, three methods of analysis were studied on eight different types of foods. The methods were (i) the Shipton's modification of the Monier-Williams' method or the Shipton method, (ii) the modified Rankine method, and (iii) the Iodine distillation method. The eight types of foods were meehoon, orange cordial, mashed potato (granule), pickled nutmeg, strawberry jam, mayonnaise, orange juice and wine. Comparative studies showed that the Iodine distillation method gave the highest mean values followed by the Shipton and modified Rankine methods, and this was true for seven out of the eight types of food studied. Recovery studies showed that the Shipton method was reliable for foods with sulphur dioxide content of more than 50 ppm, namely meehoon, cordial, mashed potato (granule) and pickled nutmeg. The second phase focussed on the study of methods for foods with less than 50 ppm, that is strawberry jam, mayonnaise, orange juice and wine. The methods were (i) the Shipton method, and (ii) the Wedzicha method. Comparative studies showed that results obtained by the Shipton method were higher than those obtained by the Wedzicha method, and this was true for all the foods studied. From the recovery studies, it was found that the Wedzicha method was the method of choice for foods with less than 50 ppm of sulphur dioxide although it is also reliable for foods which contain more than 50 ppm sulphur dioxide. The correlation between the Shipton and Wedzicha methods were studied in the third phase ofthe study. It was observed that the methods showed good correlation for foods with sulphur dioxide content of more than 200 ppm, moderate correlation for food with sulphur dioxide content of between 50 - 200 ppm and bad correlation for food with sulphur content of less than 50 ppm. The prevalence of sulphur dioxide in eighty-six types of foods were studied in the last phase. It was found that 30.23% ofthe foods contravene the Food Regulations 1985 in the sulphur dioxide content. The estimate of the Daily Dietary Intake (DDI) was calculated and it was much lower than the Acceptable Daily Intake (ADI) for sulphur dioxide.